A new design of organic radical batteries (ORBs): carbon nanotube buckypaper electrode functionalized by electrografting1. Issue 45 (7th June 2015) - Aqil, Abdelhafid; Vlad, Alexandru; Piedboeuf, Marie-Laure; Aqil, Mohamed; Job, Nathalie; Melinte, Sorin; Detrembleur, Christophe; Jérôme, Christine
<x xml:space="preserve">Abstract</x> A novel hybrid material displaying a fast and reversible charge storage capability is prepared by electrografting of an alkoxyamine-bearing acrylate onto a carbon nanotubes buckypaper.